2021
DOI: 10.1007/s11368-021-03026-6
|View full text |Cite
|
Sign up to set email alerts
|

Prokaryotic community diversity in the sediments of saline lagoons and its resistance to seasonal disturbances by water level cycles

Abstract: Purpose Apart from having high concentrations of salt, some natural saline wetlands also go through cyclical fluctuations in water level. They are frequently considered vulnerable habitats. In the last decades, the reduction of rainfall in many areas, coupled with fertilizer overuse, is transforming wetlands, especially in climates with a pronounced dry season. We studied a seasonally flooded saline wetland, and focused on the changes in the microbial communities. Methods High-throughput sequencing was used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 56 publications
1
7
0
Order By: Relevance
“…The results revealed that Proteobacteria, Chloroflexi, Bacteroidetes and Planctomycetes are the dominant taxa, followed by Spirochaetae, Acidobacteria, Actinobacteria, Cyanobacteria and Verrucomicrobia ( Cadena et al, 2019 ). Sáenz de Miera et al (2021) collected sediments from four lagoons of Spain, including Barillos, Salina Grande, Villarrin and Villalpando. Proteobacteria was identified as the most abundant phylum in all lagoons, except for Grande, where Chloroflexi was more abundant than Proteobacteria despite insignificant differences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results revealed that Proteobacteria, Chloroflexi, Bacteroidetes and Planctomycetes are the dominant taxa, followed by Spirochaetae, Acidobacteria, Actinobacteria, Cyanobacteria and Verrucomicrobia ( Cadena et al, 2019 ). Sáenz de Miera et al (2021) collected sediments from four lagoons of Spain, including Barillos, Salina Grande, Villarrin and Villalpando. Proteobacteria was identified as the most abundant phylum in all lagoons, except for Grande, where Chloroflexi was more abundant than Proteobacteria despite insignificant differences.…”
Section: Discussionmentioning
confidence: 99%
“…More insights in the microbial community are critical for understanding the functions of lagoon ecosystem. For instance, Sáenz de Miera et al (2021) reported that the seasonal disturbance of water level cycles is the major determinant of microbial community structure in sediments of saline lagoons located in the northwest of Spain. Ben Salem et al (2019) revealed bacterial community assemblages in sediments under high anthropogenic pressure at Bizerte Lagoon hydrological system, Tunisia.…”
Section: Introductionmentioning
confidence: 99%
“…The investigation of microorganisms in hypersaline settings has garnered significant interest from scientists. The majority of studies on the microbial ecology of hypersaline habitats have concentrated on saline soils, saline lakes and solar salterns [ 6 , 10 , 11 , 12 , 13 , 14 , 15 ]. As an important representative of the hypersaline environment, microbial patterns within the high-altitude salt mine aquatic ecosystems have received less attention [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the diversity of microorganisms in various hypersaline environments has been studied, but these studies have mainly focused on saline lakes, solar salterns, saline soils (Ben Abdallah et al, 2018;Gomez-Villegas et al, 2018;Bachran et al, 2019;Couto-Rodríguez and Montalvo-Rodríguez, 2019;Nan et al, 2020;Sáenz de Miera et al, 2021). It is worth noting that salt mine, a unique habitat formed tens of millions of years ago, is also an important representative of the hypersaline environment (Chen et al, 2019).…”
Section: Introductionmentioning
confidence: 99%